The effect of histamine and cyclic adenosine monophosphate on myosin light chain phosphorylation in human umbilical vein endothelial cells. - Moy, A B (1993)
Histamine causes adjacent endothelial cells to retract from each another. We examined phosphorylation of the 20-kD myosin light chain (MLC20) in human umbilical vein endothelial cells (HUVECs) exposed to histamine to determine if we could find evidence to support the hypothesis that retraction of these cells in response to histamine represents an actomyosin-initiated contraction of the endothelial cytoskeleton. We found that MLC20 in HUVECs was constitutively phosphorylated with approximately 0.2 mol phosphate/mol MLC20. Histamine increased MLC20 phosphorylation by 0.18 +/- 0.05 mol phosphate/mol MLC20. This peak increase in phosphorylation occurred 30 s after initiating histamine exposure, persisted through 90s, and returned to control levels by 5 min. Agents that increase HUVEC cAMP prevent cell retraction in response to histamine. An increase in HUVEC cAMP decreased MLC20 phosphorylation by 0.18 +/- 0.02 mol phosphate/mol MLC20 and prevented the increase in MLC20 phosphorylation after exposure to histamine. Tryptic peptide maps of phosphorylated myosin light chain indicated that myosin light chain kinase phosphorylated MLC20 in HUVECs under basal, cAMP-, and histamine-stimulated conditions. Phosphoaminoacid analysis of the monophosphorylated peptide indicated that, in contrast to smooth muscle cells, ser19 and thr18 monophosphorylation occurs in HUVECs. On the basis of our results, modulation of myosin light chain kinase activity may be an important regulatory step in the control of endothelial barrier function.